2019
DOI: 10.12659/msm.913308
|View full text |Cite
|
Sign up to set email alerts
|

High Metastasis-Associated Lung Adenocarcinoma Transcript 1 (MALAT1) Expression Promotes Proliferation, Migration, and Invasion of Non-Small Cell Lung Cancer via ERK/Mitogen-Activated Protein Kinase (MAPK) Signaling Pathway

Abstract: Background In present study, we explored the function of the metastasis-associated lung adenocarcinoma transcript 1 ( MALAT1 ) gene in the development of non-small cell lung cancer (NSCLC). Material/Methods qRT-PCR was used to detect the MALAT1 mRNA expression level in cancer tissues and adjacent normal tissues of 115 NSCLC patients and in cell lines. MALAT1 -mimic, MALAT1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Recently, several reports revealed that lncRNA Metastasis-Associated Lung Adenocarcinoma Transcript 1 (MALAT1) has crucial functions in malignant cancer progression 12 . Extensive evidence has shown that MALAT1 is aberrantly expressed in a broad range of human malignancies, including lung cancer 13 , 14 , pancreatic cancer 15 , 16 , cervical cancer 17 , breast cancer 18 , 19 , osteosarcoma 20 and ESCC 12 . MALAT1 regulates tumor progression by various signaling pathways and mechanisms, particularly EMT 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several reports revealed that lncRNA Metastasis-Associated Lung Adenocarcinoma Transcript 1 (MALAT1) has crucial functions in malignant cancer progression 12 . Extensive evidence has shown that MALAT1 is aberrantly expressed in a broad range of human malignancies, including lung cancer 13 , 14 , pancreatic cancer 15 , 16 , cervical cancer 17 , breast cancer 18 , 19 , osteosarcoma 20 and ESCC 12 . MALAT1 regulates tumor progression by various signaling pathways and mechanisms, particularly EMT 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, KCNQ1OT1 indicated a better prognosis in lung cancer 51 . MALAT1 promoted the proliferation and invasion of NSCLC 52 . Finally, a prognosis-associated TPX2-DEmiRNA-DElncRNA network in LUAD was established.…”
Section: Discussionmentioning
confidence: 93%
“…Further, high plasma miR-21 can reveal the distant metastasis of NSCLC patients [160]. The expression of MALAT1 is significantly high in NSCLC tissues and cell lines [161]. MALAT1 can enhance A549 cell invasion and migration by repressing miR-200a-3p [162].…”
Section: Resultsmentioning
confidence: 99%